Ivy League Experience: Increasing Care, Increasing Engagement - Mata, Jr., Silvester G. (Journal of International Students, 2017)
The purpose of this personal narrative is to document initiatives that were designed and implemented to increase engagement and inclusivity for international students. The university campus of focus is a historically elite institution that enrolls one out of five international undergraduate students when compared to domestic peers. Initiatives focused on welcome events (i.e., orientation, campus tours, student panels) were implemented along with initiatives focused on student mental health and student wellness. Successful initiatives utilized campus resources such as university crisis and alert teams in addition to campus resources focused on counseling and student health.